Selección de introducciones de cucurbita por contenido de aceite en semillas (2014)
Variability in fruit and seed composition of Cucurbita spp. allows inquiring about characteristics of agro-industrial importance, such as the oil content, which classifies as oilseed of economic interest. This paper presents the results obtained from the characterization and evaluation for content of ether extract (E.E.) of 277 accessions of butternut squash Cucurbita spp. from different geographical origins. The average content of ether extract (EE) was of 35.44% with a coefficient of variation (VC) of 12.60%, in addition, was evaluated the variable weight of seed per fruit (PSPF) as a component of performance, resulting in an average of 59.79%. An analysis of variance showed highly significant differences (p